Variability of sugarcane smut pathogen, Ustilago scitaminea sydow in the Philippines (2012)
This study was conducted to evaluate the variability of sugarcane smut pathogen, Ustilago scitaminea sydow in the Philippines using molecular, pathogenicity and morphological approaches. Ninety six isolates of the smut fungus collected from 17 sugarcane growing areas in the Philippines were analyzed for their polymorphism at 10 microsatellite loci. Cluster analysis among isolates was derived using simple matching coefficient. Principal component analysis was also done to structure the different U. scitaminea isolates. From both analysis, there were three major cluster groups, (A, B, C) observed, while clustering based on geographic origin was not evident. AMOVA results for the Simple Sequence Repeats (SSR) data indicated that the within population variance accounted for 76% of the total genetic variation, while the among population variance accounted for 21% of the variation. Only 3% of the variation was attributed to the among group of islands. Highly significant (P<0.01) effect of variety, isolate, and variety x isolate interactions were observed for virulence and aggressiveness of eight representative isolates using five differential hosts. The sizes and shapes of teliospore and sporidia of U. scitaminea tended to show similarity among isolates. The different isolates of U. scitaminea did not vary much in morphology as to indicate specialization. Based on the three categories established as, R (Resistant), I (Intermediate) and S (Susceptible), there were seven distinct groups of isolates producing distinct reaction types on the five differential varieties indicating that isolates of U. scitaminea in the Philippines were highly diverse and race of the fungus probably existed.